Políticas públicas para a garantia dos direitos de aprendizagem matemática - Silveira, Michele de Souza (2015)
This paper is about a research that raises questions on reform of educational public policies aimed at continuing education of teachers who teach mathematics in the early years, the Pacto Nacional Pela Alfabetização na Idade Certa (PNAIC), understanding its implications, its association with the process improvement of teaching practices developed by teachers in their school routine, which offer the student the possibility of appropriating mathematics literacy through an educational sense to him. This means that mathematics at school tends to make more sense when it provides the basic mathematical tools students for the development of mathematical thinking, they are always supported in their social practices. For this, it is necessary to analyze the influence of these policies on the qualitative aspect of the practices in the classroom. Thus, the final product of this work culminated in the form of an account of the pedagogical praxis of the teachers who teach mathematics in the early years, published in 2015, in the book Educação em Movimento: Artigos e relatos de experiências do Pacto Nacional para a Alfabetização na Idade Certa no Rio de Janeiro em 2014, with support from the Faculty of Education - UFRJ and Jose Bonifacio University Foundation.